Sensing of joint and spinal bending or stretching via a retractable and wearable badge reel - Chengyu Li (Nature Portfolio, 2021)
Human motions often contain information that is useful for orthopedic/neural disease diagnosis, rehabilitation, and prevention. Here, the authors show a badge-reel-like stretch sensing device with a grating-structured triboelectric nanogenerator for joints/spine bending or stretching sensing.